Analyzing Earnings Response Coefficient - Putri Irene s; Atik Djajanti (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: This study examines how capital structure, default risk, and earnings volatility affect the Earnings Response Coefficient (ERC) of property and real estate firms listed on the Indonesia Stock Exchange (BEI) from 2019 to 2024, with profitability as a moderating factor.